Kearifan Lokal dalam Reyog Ponorogo untuk Memperkuat Kerukunan Umat Beragama: The Local Wisdom in Reyog Ponorogo to Strengthen the Harmony of the Religious Communities - Pratama, Arga Putra (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
An option to be taken in providing multicultural education is to (re)-introduce local wisdom already existing in each communities. In Ponorogo regency of East Java province, Indonesia, its most prominent traditional dance, Reyog Ponorogo, might serve as a reflection of local wisdom in maintaining religious harmony. By conducting a qualitative research method, through interviewing relevant informants combined with articles related to the research topic, this research has found that the values contained in Reyog Ponorogo tradition range many aspect of local wisdom, expecially the value of harmony and the value of togetherness. Both of these are forms of behavior that reflect tolerance